Utilization of Digital Tafsir Al-Mishbah in Quranic Interpretation Learning at Darul Maarif Islamic College, Pattani, South Thailand - Febriani, Ina Salmah; Ngaisah, Siti; Kama Waduereh, Mustafa (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2025)
Abstract: This article discusses the method of learning tafsir at Darul Maarif College (Petidam) Thailand. The main focus of this research is to understand the learning method of Al-Quran interpretation in Petidam and how respondents respond after using digital Tafsir Al-Mishbah (TAM). The method used in this research is a qualitative approach through observation, interviews and direct documentation in Petidam, July 15-19, 2024. The result of this research is that the learning method of Al-Quran interpretation is still using classical methods with reference to one book of interpretation, Shafwatutafasir written by Imam Ali Ash-Shabuny. From the results of interviews with 20 respondents after practicing learning the digital TAM application, it was recorded that respondents have got adventages from the digital TAM application. Because it is not only an interpretation but also contains asbabunnuzul, sirah of the prophet, worship, sharia and fiqh. However, some participants also felt two difficulties. First, it is difficult to download the digital TAM application via the Appstore. Second, they still find it difficult to understand the content of the digital TAM application due to language limitations. They suggested that the digital Al-Mishbah interpretation application could be equipped with various languages, especially Thai Malay so that it could be more easily understood.